Incorporating Local Cultural Values in English Teaching Materials: A Lecturers’ Perception - Sushy Teko Patanduk; Syarifuddin Dollah; La Sunra La Sunra; Rachel Rachel; Normalia Sirande; Aprisel Bimbang Duapadang (Universitas Cokroaminoto Palopo, 2025)
This study explores lecturers' perceptions of integrating local cultural values into English teaching materials. The research aims to examine how cultural elements are utilized to enhance student engagement, foster critical thinking, and preserve local heritage while teaching English. Using a quantitative approach, data were collected through a questionnaire distributed to 6 lecturers from English Education Study Program of UKI Toraja. The findings reveal that lecturers perceive the integration of local culture as a significant pedagogical tool. A majority believe that it enhances the relevance of learning materials, creates a more inclusive classroom environment, and promotes cultural awareness among students. Additionally, incorporating cultural values is seen as a way to bridge local and global perspectives, encouraging character building and fostering values such as tolerance and empathy. This study underscores the importance of cultural integration in language education, emphasizing its potential to provide both linguistic and cultural benefits. The findings highlight the lecturers' commitment to holistic education that balances the preservation of local identity with the demands of global communication.